Archaeological Clothing Fragments from Turku - Hörkkö, Henna (My University, 2023)
The purpose of this study is to gain an understanding on medieval dress in Turku by examining archaeological textile remains. The textile fragments in question come from the 1998 excavation conducted on the locality occupied by the Åbo Akademi University, a medieval excavation that yielded a large amount of archaeological material dated to the 14th to 16th centuries. The textile fragments chosen to this study all bear some marks that suggest they once belonged to items of clothing; buttonholes, pleating, seamlines, hems, slits, other signs of sewing, and wear and tear that is due to everyday use as clothing. The aim is to identify the garments that the studied fragments belonged to. Comparative archaeological textile material and pictorial sources are the main sources in this attempt. Technical properties of the textiles are used in further aid of identification; yarn direction, density, and quality of weaving and sewing. The textile material has shown that dress in Turku was similar to that in neighbouring countries and followed the lines of European fashions. While the cut of garments was often complicated, even sophisticated, the quality of fabrics was rough and coarse. There were exceptions, however, with some high quality, foreign import fabrics being used for clothing. The fragments were shown to having been disposed in a way that allowed for the majority of the garment to be refashioned; seams, hems and cuffs were the usual parts to be cut off. Being clothed was economical, and the garments and fabrics were used as long as possible.
Keywords: Middle Ages, Turku, archaeological textiles, medieval clothing, textile studies, life cycle, fashion, medieval garments, medieval dress, tailoring, dressmaking